2018
DOI: 10.1186/s12967-018-1471-1
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin based therapy: the role of the mitogen activated protein kinase signaling pathway

Abstract: Cisplatin is a widely used chemotherapeutic agent for treatment of various cancers. However, treatment with cisplatin is associated with drug resistance and several adverse side effects such as nephrotoxicity, reduced immunity towards infections and hearing loss. A Combination of cisplatin with other drugs is an approach to overcome drug resistance and reduce toxicity. The combination therapy also results in increased sensitivity of cisplatin towards cancer cells. The mitogen activated protein kinase (MAPK) pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
99
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(100 citation statements)
references
References 103 publications
0
99
0
1
Order By: Relevance
“…It has been reported that cisplatin resistance in HCC may occur through the loss of Runt-associated transcription factor 3 and upregulation of cyclophilin B (21,22). Recently, certain key biomarkers of cisplatin resistance have revealed novel molecular mechanisms of resistance (23). The role of circRNAs in the development of chemotherapeutic drug resistance has also been highlighted (24-26).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that cisplatin resistance in HCC may occur through the loss of Runt-associated transcription factor 3 and upregulation of cyclophilin B (21,22). Recently, certain key biomarkers of cisplatin resistance have revealed novel molecular mechanisms of resistance (23). The role of circRNAs in the development of chemotherapeutic drug resistance has also been highlighted (24-26).…”
Section: Discussionmentioning
confidence: 99%
“…Cisplatin (CP) is a potent antineoplastic agent that is widely used to treat various types of tumors (1,2). However, its clinical application is limited by time-and dose-dependent nephrotoxicity, which is associated with high morbidity and mortality (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…2 The mammalian target of rapamycin (mTOR) is a serine/threonine protein kinase that controls cell proliferation and survival. Cisplatin triggers cell apoptosis by binding to DNA and crosslinking the DNA strands.…”
Section: Introductionmentioning
confidence: 99%
“…Several strategies can overcome cisplatin drug resistance and toxicity, including liposome delivery, inhibition of glutathione and metallothionein species, and combination therapy. 2 The mammalian target of rapamycin (mTOR) is a serine/threonine protein kinase that controls cell proliferation and survival. AKT1 overexpression and gene amplification have been shown to induce lung cancer cells to become resistant to cisplatin through mTOR signaling pathway.…”
Section: Introductionmentioning
confidence: 99%